Physical Address
Suite 5, 181 High Street,
Willoughby North NSW 2068
Physical Address
Suite 5, 181 High Street,
Willoughby North NSW 2068
Integrating functions is one of the core applications of calculus. Sometimes, this is straightforward, as in:
(F(x) = int( x^3 + 8) dx)
In a comparatively complicated example of this type, you can use a version of the basic formula for integrating indefinite integrals:
(int (x^n + A) dx = frac{x^{(n + 1)}}{n + 1} + Ax + C)
where A and C are constants.
Thus for this example,
(int x^3 + 8 = frac{x^4}{4} + 8x + C)
On the surface, integrating a square root function is awkward. For example, you may be stymied by:
(F(x) = int sqrt{(x^3) + 2x – 7}dx)
But you can express a square root as an exponent, 1/2:
(sqrt{x^3} = x^{3(1/2)} = x^{(3/2)})
The integral therefore becomes:
(int (x^{3/2} + 2x – 7)dx)
to which you can apply the usual formula from above:
(begin{aligned}int (x^{3/2} + 2x – 7)dx &= frac{x^{(5/2)}}{5/2} + 2bigg(frac{x^2}{2}bigg) – 7x)(&= frac{2}{5}x^{(5/2)} + x^2 – 7xend{aligned})
Sometimes, you may have more than one term under the radical sign, as in this example:
(F(x) = int frac{x + 1}{sqrt{x – 3}}dx)
You can use u-substitution to proceed. Here, you set u equal to the quantity in the denominator:
(u = sqrt{x – 3})
Solve this for x by squaring both sides and subtracting:
(u^2 = x – 3)(x = u^2 + 3)
This allows you to get dx in terms of u by taking the derivative of x:
(dx = (2u)du)
Substituting back into the original integral gives
(begin{aligned})(F(x) &= int frac{u^2 + 3 + 1}{u}(2u)du)(&= int frac{2u^3 + 6u + 2u}{u}du)(&= int (2u^2 + 8)du)(end{aligned})
Now you can integrate this using the basic formula and expressing u in terms of x:
(begin{aligned})(int (2u^2 + 8)du &= frac{2}{3}u^3 + 8u + C)(&= frac{2}{3} (sqrt{x – 3})^3 + 8( sqrt{x – 3}) + C)(&= frac{2}{3} (x – 3)^{(3/2)} + 8(x – 3)^{(1/2)} + C)(end{aligned})